Contribution of biogas use on forest conservation - Shrestha, Ishu; Ghimire, Pramod; Bhatta, Balram (Journal of Agriculture and Natural Resources, 2019)
Biogas is an eco-friendly alternative energy source which can greatly contribute to reducing greenhouse gases as they have the possibility of reducing the need to use fossil fuels. A study was conducted at Kumroj village of Khairhani municipality, of Chitwan district of Nepal to assess the sources of energy, dependency of local people on biogas, amount of fire wood substituted by biogas and people’s perception towards biogas use and forest conservation. Stratified random sampling method was used for sampling design. Direst field observation, households questionnaire survey (n=44), key informant interview, and focus group discussions were used for data collection. This study showed that the main source of energy was firewood for cooking, preparation of animal feed, preparation of alcohol and water heating but now these days the dependency on firewood decreased after use of biogas. About 63.6% of the household were using biogas as an alternative source of energy. The need of biogas was always higher during winter while production of gas was lower in compare to summer season. According to gas users, it reduced the fuel wood consumption, improved the kitchen environment, saved time in fuel wood collection and cooking, and also reduced the health problems. The average reduction in fuel-wood consumption was 42.8% after the installation of biogas. All the respondents were agreed that condition of forest was improving. The reason behind this was the use of biogas which reduces the pressure on the fuel-wood collection and ultimately helps in forest conservation.